La monografia digitale: pratiche, potenzialità e prospettive di rinnovamento - Di Tella, Alessandra (Umanistica Digitale, 2018)
The topic of form, publication and fruition of the academic monograph in the humanities is not enough investigated in his peculiarities, neither quantitatively nor qualitatively. Starting from the lacks in literature and from the stasis of the monographic genre, the article means to achieve a critical investigation of the state of the art and then explores new possibilities and developments linked to the digital. The aim is to focus especially on the new forms of liquid and multimodal text based on the Digital Humanities paradigms, that let us rethink the composition and publication of the print-based model of essays. The article reviews some of the major publishing experimentations and makes a comparison with the case of excellence of Stanford University Press Digital project. In the end, it attempts to set some guidelines for a model of born-digital monograph that is sustainable and evaluable, and represent a structural innovation in the field of scholarly communication.